Chemically Crosslinked Hydrogel Film Leads to Integrated Flexible Supercapacitors with Superior Performance. (15th October 2015) - Wang, Kai; Zhang, Xiong; Li, Chen; Sun, Xianzhong; Meng, Qinghai; Ma, Yanwei; Wei, Zhixiang
Abstract : A high‐strength poly(vinyl alcohol) chemical hydrogel (PCH) film is prepared by coupling covalent crosslinking with a film‐casting process. Conducting polyaniline (PANI) is then embedded in the PCH film by in situ growth to form a composite film with a PANI–hydrogel–PANI configuration, which leads to a new conceptual flexible supercapacitor with all‐in‐one configuration that exhibits superior electrochemical performance and mechanical flexibility.